2019
DOI: 10.1017/ice.2019.258
|View full text |Cite
|
Sign up to set email alerts
|

Reducing unnecessary urethral catheter use in Japanese intensive care units: A multicenter interventional study

Abstract: We conducted a preintervention–postintervention study to assess the effectiveness of a multimodal approach to reduce unnecessary urethral catheters in 5 Japanese intensive care units. After the intervention urethral catheter point prevalence decreased by 18%, from 79% preintervention to 61% postintervention, and catheter appropriateness increased by 28%, from 57% preintervention to 85% postintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The CAUTI incidence (CAUTI per 1000 catheter-days) was also higher than reports from the US (1.54–2.28) [ 1 ], Korea (1.6) [ 16 ], and The Netherlands (4.0 infections per 1000 catheter-days) [ 14 ]. Multimodal approaches to promote prompt urinary catheter removal when no longer appropriate have shown success in both Japan and the US [ 1 , 9 , 10 ]. These approaches frequently include nurse-initiated catheter removal when deemed no longer appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAUTI incidence (CAUTI per 1000 catheter-days) was also higher than reports from the US (1.54–2.28) [ 1 ], Korea (1.6) [ 16 ], and The Netherlands (4.0 infections per 1000 catheter-days) [ 14 ]. Multimodal approaches to promote prompt urinary catheter removal when no longer appropriate have shown success in both Japan and the US [ 1 , 9 , 10 ]. These approaches frequently include nurse-initiated catheter removal when deemed no longer appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The study data collection tool was similar to those used for other studies and can be found in Additional file 1 : Appendix S1 [ 7 , 9 , 10 ]. To assess prevalence, the observer rounded at fixed times and visited each patient on the ward each assessment day to visually confirm the presence or absence of a urinary catheter.…”
Section: Methodsmentioning
confidence: 99%
“…Initiatives aimed at preventing CAUTIs, including adding a stop order, reminders, and hygiene protocols, have been proven to be effective [4]. Most successful preventative initiatives implemented safety bundles that included an educational component or a training session, which were both time-consuming and required funding [5,6] the effectiveness of modifying access to urinary catheter placement kits on medical-surgical floors that showed a significant reduction in unnecessary Foley placements and reduction in CAUTI rates. While our single-center study showed promising results, it is limited by the small sample size; therefore, larger studies are needed to further evaluate effectiveness of this intervention.…”
Section: Dear Editormentioning
confidence: 99%
“…Many devices are not promptly removed when no longer needed, with reports that up to 50% of PIVCs (Becerra et al, 2016), 32% of CVADs (Kara et al, 2016), and between 31%-45% of IUCs (Corral-Gudino et al, 2019;Kuriyama et al, 2019;Laan et al, 2020) are left in place without medical indication, increasing risk of infection. Reasons for leaving devices in situ unnecessarily include inaccurate documentation; perceptions of patient comfort; lack of priority for device removal; lack of agreement on indications for removal; and confusion regarding staff authority to remove unneeded devices (Bourgault et al, 2021;Castro-Sanchez et al, 2014;Quinn et al, 2020).…”
Section: Does the Patient Need This Device?mentioning
confidence: 99%
“…Daily assessment of invasive devices for continued need and early detection of complications enhances patient safety. Implementation studies of multimodal bundles, including daily prompts of device necessity, have achieved reduction in utilization of IUCs (Gazarin et al, 2020;Giles et al, 2020;Kuriyama et al, 2019;Niederhauser et al, 2019;Schweiger et al, 2020), CVADs (Kara et al, 2016;Kleinman Sween et al, 2021;Walz et al, 2015;Xiong & Chen, 2018), CVADs and IUCs (Chandramohan et al, 2018;Kaminski et al, 2021;Mena Lora et al, 2020), IUCs and PIVCs (Laan et al, 2020), andPIVCs (Egerton-Warburton et al, 2019;Mestre et al, 2013;Yagnik et al, 2017). Interventions that employ education, daily reminders, and automated stop-orders demonstrate greater clinician awareness of device use and prompt removal of unnecessary devices, with subsequent reductions in complications and infections (Kleinman Sween et al, 2021;Meddings et al, 2020;Mitchell et al, 2019;Yu et al, 2020), but continued vigilance is crucial (Chandramohan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%